The Importance of Maine’s Economic Ties with Canada: Some Thoughts Related to the East-West Highway - Mueller, Richard (Maine Policy Review, 1998)
Whether to build an east-west highway across central Maine has been widely debated in recent months and, regardless of where one stands on the issue, all agree it is important to study the idea further. In this article, Richard Mueller addresses Maine’s economic linkages with Canada and assesses how an east-west highway would affect them. He focuses on cross border traffic flows, inter-provincial truck activity, Canadian-American trade, and tourism, concluding that there is little doubt an east-west highway would bring economic benefits to northern and central Maine. Yet he cautions policymakers to consider the investment carefully. Highways are two-way streets where economic benefits can enter as well as leave the state, and determining the magnitude of the costs and benefits requires further study.